Learn more about

Refine search

Results (displaying all 46 matches)

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
13696.b.109568.1 13696.b \(y^2 + x^2y = x^5 + 12x^4 - 2x^3 - 253x^2 + 288x - 83\) $\mathrm{USp}(4)$ 0
16108.b.64432.1 16108.b \(y^2 + (x^2 + x)y = 2x^5 - 32x^4 + 55x^3 - 79x^2 + 49x - 25\) $\mathrm{USp}(4)$ 0
19201.a.134407.1 19201.a \(y^2 + (x^2 + x + 1)y = x^5 - 23x^4 - 34x^3 + 10x^2 + 14x - 7\) $\mathrm{USp}(4)$ 0
22324.b.178592.1 22324.b \(y^2 + (x^2 + x)y = x^5 - 37x^4 + 232x^3 - 407x^2 - 4x\) $\mathrm{USp}(4)$ 0
32119.a.32119.1 32119.a \(y^2 + (x^2 + x + 1)y = -x^6 - 4x^5 + 4x^4 + 23x^3 - 21x^2 - 9x - 1\) $\mathrm{USp}(4)$ 0
50608.b.809728.1 50608.b \(y^2 = x^5 - 30x^3 - 72x^2 - 28x - 3\) $\mathrm{USp}(4)$ 0
59648.b.59648.1 59648.b \(y^2 + (x^2 + 1)y = x^5 + 17x^4 + 55x^3 - 179x^2 - 14x + 1\) $\mathrm{USp}(4)$ 0
64000.c.64000.1 64000.c \(y^2 + x^2y = x^5 - 10x^3 + 75x^2 + 60x - 665\) $\mathrm{USp}(4)$ 0
73990.a.369950.1 73990.a \(y^2 + xy = 5x^5 - 21x^4 - 22x^3 + 89x^2 + 104x + 14\) $\mathrm{USp}(4)$ 0
92572.a.92572.1 92572.a \(y^2 + (x^2 + x)y = x^5 - 32x^4 + 96x^3 + 23x^2 - 169x - 89\) $\mathrm{USp}(4)$ 0
96347.b.96347.1 96347.b \(y^2 + y = -18x^6 - 41x^5 + x^4 + 35x^3 - 5x - 1\) $\mathrm{USp}(4)$ 0
98091.b.686637.1 98091.b \(y^2 + (x^2 + x + 1)y = 7x^5 - 69x^4 - 95x^3 - 16x^2 + 9x - 1\) $\mathrm{USp}(4)$ 0
102591.b.307773.1 102591.b \(y^2 + y = x^5 - 79x^4 + 123x^3 - 62x^2 + 11x - 1\) $\mathrm{USp}(4)$ 0
134656.d.134656.1 134656.d \(y^2 + x^2y = x^5 + 38x^4 + 380x^3 + 272x^2 + 56x + 2\) $\mathrm{USp}(4)$ 0
154936.a.309872.1 154936.a \(y^2 + (x + 1)y = 2x^5 - 28x^3 - 54x^2 - 52x - 49\) $\mathrm{USp}(4)$ 0
179496.a.358992.1 179496.a \(y^2 + xy = 2x^5 - 16x^4 + 6x^3 + 24x^2 - 26x - 27\) $\mathrm{USp}(4)$ 0
195337.c.195337.1 195337.c \(y^2 + (x^2 + x + 1)y = x^5 - 31x^4 + 18x^3 + 29x^2 - 13x - 7\) $\mathrm{USp}(4)$ 0
235237.b.235237.1 235237.b \(y^2 + y = x^5 - 15x^4 + 22x^3 + 25x^2 - 28x - 22\) $\mathrm{USp}(4)$ 0
258357.a.258357.1 258357.a \(y^2 + x^2y = x^5 - 22x^4 - 30x^3 + x^2 + 11x + 2\) $\mathrm{USp}(4)$ 0
276124.a.276124.1 276124.a \(y^2 + (x^3 + x^2 + x)y = 3x^4 + 3x^3 + 12x^2 - x\) $\mathrm{USp}(4)$ 0
279259.a.279259.1 279259.a \(y^2 + y = x^5 + 9x^4 + 30x^3 + 28x^2 + 5x\) $\mathrm{USp}(4)$ 0
320137.a.320137.1 320137.a \(y^2 + (x^2 + x)y = x^5 - 3x^4 - 9x^3 - 4x^2 + x\) $\mathrm{USp}(4)$ 0
335164.a.335164.1 335164.a \(y^2 + (x^2 + x + 1)y = x^5 + x^4 + 2x^3 - 16x^2 + 9x + 1\) $\mathrm{USp}(4)$ 0
337355.a.337355.1 337355.a \(y^2 + y = x^5 - x^4 + 10x^3 - 16x^2 + 5x + 1\) $\mathrm{USp}(4)$ 0
342871.b.342871.1 342871.b \(y^2 + (x^2 + x + 1)y = -x^6 - 10x^5 - 23x^4 + 34x^3 + 19x^2 - 15x - 7\) $\mathrm{USp}(4)$ 0
350464.a.350464.1 350464.a \(y^2 = x^5 - 3x^4 - 11x^3 - 8x^2 - x\) $E_6$ 0
354069.a.354069.1 354069.a \(y^2 + y = x^5 + 16x^4 + 8x^3 + 5x^2 + x\) $\mathrm{USp}(4)$ 0
356211.b.356211.1 356211.b \(y^2 + y = x^5 - 52x^4 + 57x^3 - 9x^2 - 3x - 1\) $\mathrm{USp}(4)$ 0
362107.a.362107.1 362107.a \(y^2 + y = x^5 - 43x^4 - 75x^3 - 41x^2 - 8x - 1\) $\mathrm{USp}(4)$ 0
444277.a.444277.1 444277.a \(y^2 + x^2y = x^5 - 13x^4 + 28x^3 + 82x^2 + 7x - 34\) $\mathrm{USp}(4)$ 0
449957.d.449957.1 449957.d \(y^2 + xy = x^5 + 20x^4 + 42x^3 + 24x^2 + x\) $\mathrm{USp}(4)$ 0
461180.a.461180.1 461180.a \(y^2 + (x^3 + 1)y = 3x^4 + 3x^3 + 9x^2 + 20x + 11\) $\mathrm{USp}(4)$ 0
484013.a.484013.1 484013.a \(y^2 + y = x^5 - 3x^4 - 15x^3 + 17x - 7\) $\mathrm{USp}(4)$ 0
493528.a.987056.1 493528.a \(y^2 + xy = 2x^5 - 27x^4 + 15x^3 - 162x^2 + 27x - 242\) $\mathrm{USp}(4)$ 1
495324.a.495324.1 495324.a \(y^2 + (x^2 + x + 1)y = x^5 + 12x^4 + 45x^3 + 38x^2 - 7x\) $\mathrm{USp}(4)$ 0
537289.a.537289.1 537289.a \(y^2 + (x^2 + x)y = x^5 - 9x^4 + 12x^3 - 4x^2 - x\) $E_6$ 0
543321.a.543321.1 543321.a \(y^2 + (x^2 + x + 1)y = x^5 - 8x^4 - 3x^3 - 6x^2 + 4x - 1\) $\mathrm{USp}(4)$ 0
574220.a.574220.1 574220.a \(y^2 + (x^2 + x + 1)y = -x^6 + 4x^4 - 22x^3 - 2x^2 + 76x - 59\) $\mathrm{USp}(4)$ 0
662773.a.662773.1 662773.a \(y^2 + y = x^5 + 25x^4 - 20x^3 + 9x^2 - 2x\) $\mathrm{USp}(4)$ 0
754714.a.754714.1 754714.a \(y^2 + (x^2 + x)y = x^5 - 30x^4 + 219x^3 + 26x^2 + x\) $\mathrm{USp}(4)$ 0
779665.a.779665.1 779665.a \(y^2 + xy = x^5 - 17x^4 + 81x^3 - 60x^2 - 118x - 33\) $\mathrm{USp}(4)$ 0
820897.b.820897.1 820897.b \(y^2 + (x^2 + x + 1)y = x^5 - 9x^4 - 4x^3 + 20x^2 - 5x\) $\mathrm{USp}(4)$ 0
853157.a.853157.1 853157.a \(y^2 + x^2y = x^5 + 16x^4 + 56x^3 - 87x^2 - 53x - 7\) $\mathrm{USp}(4)$ 0
858491.a.858491.1 858491.a \(y^2 + (x^2 + 1)y = x^5 - 8x^4 + 13x^3 + 83x - 212\) $\mathrm{USp}(4)$ 0
931349.a.931349.1 931349.a \(y^2 + x^2y = x^5 - 5x^4 - 18x^3 + 17x - 6\) $\mathrm{USp}(4)$ 0
967723.a.967723.1 967723.a \(y^2 + xy = x^5 + 2x^4 - 6x^3 - 13x^2 - x\) $\mathrm{USp}(4)$ 0


Download all search results for